Applying the exponential smoothing model for forecasting tourists' arrivals: Example of Novi Sad, Belgrade and Niš - Vujko Aleksandra; Papić-Blagojević Nataša; Gajić Tamara (Ekonomika Poljoprivrede (1979), 2018)
Predicting future movements of tourism demand based solely on the past behaviour of variables such as number of overnight stays is crucial for the development of tourism and mitigation of seasonality. Nowadays, there are many different models that could be used for forecasting. Sometimes, some simpler models could fit better to collected data and, in the other hand, more sophisticated ones are more convenient. In this paper, the exponential smoothing models have been applied on the data that was taken from Republic Statistical Office (RSO). The research was conducted on monthly data relating to the number of overnight stays in Belgrade, Novi Sad and Niš during the period from January 2000 to December 2013. Based on the selected data, forecasting was made for overnight stays until May 2018. It is concluded that the selected models correspond to the observed data, and the precision of the obtained predictions is determined by comparing the BIC precision measures.